Displaced academics: intended and unintended consequences of the changing landscape of teacher education. Issue 1 (1st January 2022) - Kosnik, Clare; Menna, Lydia; Dharamshi, Pooja
ABSTRACT: Given the intense politicisation of education, many teacher educators are caught in the cross-hairs of government's reform agendas, university expectations and student teacher needs. This paper reports on a study of 28 literacy teacher educators in four countries (Canada, US, Australia and England). This paper reports on the broad question: How is politics affecting literacy teacher educators? Three specific aspects are considered: their pedagogies, identity and well-being. It describes how their pedagogy (goals and teaching strategies) has narrowed because of mandated curriculum and exit exams. It shows how their identity as academics is being complicated because they often do not have time for their research. And their well-being is compromised because of excessive external inspections and as their community in the university splinters.